Do Academic Recruitment Policies Under Represent Teaching and Learning Competences? - Thomson, Gareth; Kövesi, Klara (CCSD, 2022)
International audience CDIO standards 9 and 10 focus on the technical and teaching competences of staff delivering engineering education programmes. For most Universities, whether CDIO or otherwise teaching and learning are the key financial and reputational activities which ensure the institution can thrive. To ensure academic degrees can be delivered in a progressive, student centered and active manner such as that championed by CDIO it is essential that staff with the capabilities to deliver and develop strong teaching and learning approaches are recruited and trained. This paper looks at recruitment practices for Engineering academics in the UK and France. It examines how research and teaching criteria are framed in the hiring process examining recruitment advertisements and job details to examine both the numbers and types of terms used to describe these two types of core academic activities. This tends to show that, while anecdotally it has always been reported, for many of the more established Universities there is a significantly greater emphasis on research over teaching competences though the picture is not uniform and while the picture in France and the UK overall is similar the degree of emphasis of research over teaching in France appears lower.